Design of 1 435/1 000 mm Gauge Changeable Bogie for EMUs - Fang XU; Zhihui HUANG; Ruizhuo WANG; Wenxue LI; Xiantao XIN; Hongwei CUI (机车电传动)
Based on current technology and vehicle type of EMUs, a new gauge changeable bogie structure was proposed according to technical specification of 1 435/1 000 mm gauge changeable bogie. Further introduction and analysis about overall structure, frame, wheelset, primary suspension device, secondary suspension device, foundation brake rigging and the theory of gauge changeable bogie was presented. Besides, dynamic performance of overall vehicle was simulated and finite element calculation of gauge changeable bogie’s critical components was analyzed. The calculation results indicated that this new gauge changeable bogie structure was feasible, met relevant standards and design requirements.